Skills Based Competency dan Daya Saing Praktisi Akuntansi Pada Emerging Market Asean - Sanusi Gazali Pane; Saparuddin Siregar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The competency framework is needed by accounting practitioners in organizations to carry out their roles effectively. Moreover, in the context of economic integration and labor mobility between regional countries, the role of accounting practitioners is one of the eight professions affected by professional competition. The purpose of this study was to measure the level of competence of accounting practitioners by using a competency assessment method that refers to technical and non-technical assessments through collecting relevant evidence on accounting work. The results of this study indicate that during the 2018-2020 testing period, 83.01 failed to meet the competency level. Meanwhile, 16.01 percent have competency standards in accounting technician qualifications and professional clusters. The implication of this finding illustrates that the level of difficulty of labor market accessibility in the domestic and regional arena will increase and the resulting competitiveness will be lower. Controlled and relevant improvisation, especially in the world of education by directing a curriculum based on the competency framework paradigm. This concept is at least in line with the government's commitment to create superior human resources for Indonesia to grow and be more advanced.